The role of administrative governance in reforming legislation in federal states - salhe, Ban Salah Al (Journal of Legal and Political Studies, 2025)
Federal states are characterized by multiple levels of government and authorities. This multiplicity must contain and lead to sometimes fundamental and sometimes practical differences in the administrative performance of each part without affecting the remaining parts and without prejudice to the rights of the other parts and taking into consideration the subjective conditions and the general comprehensive state of the state. Several questions are raised about the competent authorities in the initial determination of governance, as well as the legislation establishing it and the valid mandate for implementation. Methods and approaches cannot be established without taking into account the degree of consistency and harmony between governments and their administration. This structure must be reinforced with areas suitable for implementation without raising endless differences or disputes. Questions are also raised about the organization of administration to provide services in their modern form, and about the activation of some legislative texts and their logical interpretation that is acceptable to all parties and is not for the benefit of one party without the other. Does administrative governance lead to effective reform of legislation? The research will also address the global development in solving the supposed and realistic problems that may hinder the application of the codified texts and how to actually apply them so that they take their proper course in the interest of citizens and serve the interests of individuals and economic activity without causing social effects. The research on the purpose of legislation is in the interest of the individuals of society, trying to provide services in a better way without affecting the lives of peoples. Keywords: Governance, Transparency, Quality, Federalism, Accountability
Keywords: Governance; Transparency; Quality; Federalism; Accountability